Psychological Capital Intrusion Towards Employee Performance and Counter Productive Behaviour - ASIA ZAMAN; MINHAS ALI KHAN; ASAD SARFARAZ KHAN (Journal of Business & Tourism, 2021)
The research study inspects the construct of three factor model i.e. Psychological Capital (PC), Counter Productive Work Behaviour (CWB) and Employee Performance (EP). Questionnaire on cross-sectional basis distributed among 285 faculty members of eight public and private universities of KP, Pakistan. Confirmatory factor analyses (CFA), structure equation modelling (SEM), multiple regression and correlation statistical tools were utilized to analyze the data. All the hypotheses of the study were supported. Study depicts that PC significantly intervene towards controlling CWB that further leads towards better EP. Recommendation and future area of research were also incorporate in the study.